2021
DOI: 10.2337/ds20-0038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Protocols to Reduce Diabetic Ketoacidosis in Patients With Type 1 Diabetes Prescribed a Sodium–Glucose Cotransporter 2 Inhibitor

Abstract: OBJECTIVE | Sodium–glucose cotransporter 2 (SGLT2) inhibitors are approved for type 1 diabetes in Europe and Japan, with off-label use in type 1 diabetes in the United States. Although there were no consistent approaches to risk mitigation in clinical trials of these agents, protocols have been developed to try to reduce the risk of diabetic ketoacidosis (DKA). However, a validated risk mitigation strategy does not exist. We reviewed available DKA risk mitigation protocols to better understand the various stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…3 However, while clinical trials showed improved glycaemic endpoints, [4][5][6] reviewed elsewhere, 7 concerns about side effects, particularly diabetic ketoacidosis (DKA), remain a major limitation. Risk-mitigation strategies have been proposed 8 ; yet, regulatory judgement of these strategies' sufficiency has differed. Whereas SGLTi use in T1D is approved in Japan and for adults with body mass index (BMI) >27 kg/m 2 in Europe, the US Food and Drug Administration (FDA) rejected similar approval requests.…”
mentioning
confidence: 99%
“…3 However, while clinical trials showed improved glycaemic endpoints, [4][5][6] reviewed elsewhere, 7 concerns about side effects, particularly diabetic ketoacidosis (DKA), remain a major limitation. Risk-mitigation strategies have been proposed 8 ; yet, regulatory judgement of these strategies' sufficiency has differed. Whereas SGLTi use in T1D is approved in Japan and for adults with body mass index (BMI) >27 kg/m 2 in Europe, the US Food and Drug Administration (FDA) rejected similar approval requests.…”
mentioning
confidence: 99%
“…The greatest concern stems from the DKA risk, which can occur without extreme hyperglycemia (euglycemic DKA), especially in the setting of "low carb" diets or low carbohydrate intake or associated with dehydration. 63,64 Any person receiving SGLT1/2 inhibitors must receive rigorous sick day management education and strategies for mitigating DKA risk need to be discussed to avoid progression to DKA. This includes training on the use of blood ketone monitoring and counseling patients that DKA may occur without severe hyperglycemia if SGLT1/2 inhibitors are being taken.…”
Section: Adjunctive Therapymentioning
confidence: 99%
“…Adjunctive use of the new class of oral agents called SGLT2 (or SGLT1/2) inhibitors have been reported to increase risk for DKA in persons with T1D or type 2 diabetes. The greatest concern stems from the DKA risk, which can occur without extreme hyperglycemia (euglycemic DKA), especially in the setting of “low carb” diets or low carbohydrate intake or associated with dehydration 63,64 . Any person receiving SGLT1/2 inhibitors must receive rigorous sick day management education and strategies for mitigating DKA risk need to be discussed to avoid progression to DKA.…”
Section: Adjunctive Therapymentioning
confidence: 99%